Embracing Resiliency: Practical Strategies to Minimize Teacher Burnout and Elevate Retention - Melissa D Reed; Heather Caswell; Monica Wong-Ratcliff (The Advocate, 2022)
Abstract Teacher shortage constitutes a crisis in the U.S. and the education system at-large. In light of the crisis of teacher shortage and the severity of turnover rate, the purpose of this paper is to join in the dialogue to further the conversation regarding how believing or reinforcing stereotypes can contribute to burnout and unrealistic expectations teachers face in education. Suggestions for pre-service and in-service teachers to acquire a more realistic and resilient lens for themselves as educators and the profession is presented. The following themes will be explored: collaboration, embracing vulnerability, empowerment and agency, support and mentoring, and self-care and resiliency.
Keywords: teacher retention; resilience; self-care; mentoring; empowerment